Digital Leadership in Driving Work Innovation: The Role of Creativity, Motivation, and Gender - Hastiti, Anisa Permata; Subiyanto, Didik; Hadi, Syamsul (Bina Nusantara University, 2025)
This research aimed to explore the role of digital leadership in promoting innovative work behaviors through the mediation of intrinsic motivation and problem-solving creativity and to analyze differences in influence based on gender. A total of 117 lecturers and education staff at private universities were analyzed through AMOS SEM to test the direct, indirect, and moderation influences of gender. The results show that digital leadership does not have a direct effect on innovative work behavior through intrinsic motivation and problem-solving creativity. Digital leadership has a positive effect on intrinsic motivation, thereby strengthening internal motivation for optimal contribution. Gender analysis reveals that digital leadership has a significant impact on intrinsic motivation and problem-solving creativity, with a stronger effect on women, particularly in increasing their intrinsic motivation. However, the relationship between problem-solving creativity and innovative work behavior remained insignificant. The implications emphasize the importance of strengthening strategic digital leadership to enhance intrinsic motivation and creativity, considering gender-based responses to drive innovative work behaviors.